Analisis Faktor-Faktor Yang Mempengaruhi Keberhasilan Usaha Pada Usaha Mikro Kecil Menengah (UMKM) Rumah Makan di Kelurahan Cilincing Jakarta Utara - Rika, Rika; Musadad, Anwar (Peneliti.net, 2025)
This research aims to find out and analyze the factors that influence business success at MSME Restaurants in Cilincing Subdistrict. This research also aims to find out and analyze which factors have a dominant influence on business success at restaurants in Cilincing Village. The method used is quantitative descriptive. This research was conducted in Cilincing Village using SPSS tools. The population in this study was 120 MSME restaurants located in Cilincing Village with a sample of 93 respondents. Based on the results of the research and discussion, it can be concluded that business success in MSME Restaurants in Cilincing Subdistrict, it is known that there are four (4) factors that are thought to encourage business success, namely potential factors, planning factors, strong determination factors and capital factors. After carrying out factor analysis, 1 factor was formed, namely the skill factor. The most dominant factor in business success is the skill factor with a total variance value of 68,751%.